Switchable Metasurface With Broadband and Highly Efficient Electromagnetic Functionality - Wei, Zeyong; Liu, Xiaoqin; Cao, Yang (Frontiers in Physics, 2020)
Electromagnetic metasurface is a kind of artificial electromagnetic structure, which can control the transmission, reflection, polarization and beam of electromagnetic wave within sub-wavelength thickness. Efficiency, bandwidth and dynamic control are very important in the application of metasurface. The bandwidth of electromagnetic transparency can be broadened by interlayer coupling of local resonance modes of the stacked layers. In this paper, we propose that the electromagnetic wave could be switched on or off in a broadband frequency range by metasurface which consists of three layers of metal microstructures with PIN diodes. When the diodes are biased with forward voltage, the switching diodes are in the on state, and the slab reflects electromagnetic wave completely, just like a perfect metal. When the diodes are biased with backward voltage, the switching diodes are equivalent to a capacitor, and all the electromagnetic wave energy passes through the sample. The simulation results show that the transmissivity is less than 1% when the sample is loaded with forward voltage in the frequency range of 8-12GHz, while the transmittance is more than 96% when the sample is loaded with reverse bias. We have fabricated the corresponding samples and measured the reflection and transmission in the waveguide. The measurements verify the properties of broadband highly efficient electromagnetic transparency and perfect reflection.